2014
DOI: 10.5694/mja13.00175
|View full text |Cite
|
Sign up to set email alerts
|

Use of advance directives by South Australians: results from the Health Omnibus Survey Spring 2012

Abstract: Completion rates of ADs among South Australians remain low, with financial instruments more likely to be completed than health care and lifestyle instruments. The odds of not completing ADs were associated with age and socioeconomic characteristics. General practitioners are in a good position to target advance care planning towards relevant patient groups, which would likely improve rates of decision making in future health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 0 publications
4
30
1
Order By: Relevance
“…A theme identified in this study is that there is a very low awareness of ACP amongst older Chinese Australians, which perhaps is expected as the awareness of ACP in the general older Australian population has also been reported to be low (Boddy, Chenoweth, McLennan, & Daly, ; Jeong, Ohr, Pich, Saul, & Ho, ). This may be exacerbated by the language barrier which contributes to the lack of access to health information by the older Chinese Australians who tend to have lower English literacy levels (Bradley et al., ; Cultural & Indigenous Research Centre Australia (CIRCA), ). The participants had varying capacity to understand health issues and varied in the degree of health awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A theme identified in this study is that there is a very low awareness of ACP amongst older Chinese Australians, which perhaps is expected as the awareness of ACP in the general older Australian population has also been reported to be low (Boddy, Chenoweth, McLennan, & Daly, ; Jeong, Ohr, Pich, Saul, & Ho, ). This may be exacerbated by the language barrier which contributes to the lack of access to health information by the older Chinese Australians who tend to have lower English literacy levels (Bradley et al., ; Cultural & Indigenous Research Centre Australia (CIRCA), ). The participants had varying capacity to understand health issues and varied in the degree of health awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Family members tend to exhibit less stress and anxiety following death of these patients (Detering et al., ). Despite its benefits, there is a low prevalence of uptake of ACP within the general population within Australia (Bradley, Woodman, Tieman, & Phillips, ). This is exacerbated in non‐English‐speaking background (NESB) communities (Johnstone & Kanitsaki, ).…”
Section: Introductionmentioning
confidence: 99%
“…The same holds true for a power of attorney (POA) for health care authorizing other persons to make medical decisions if an individual is temporarily or permanently unable to make own decisions (e.g. [25]). Both ADs and POA for health care are, moreover, part of the broader topic of advance care planning (ACP), “[…] a wider process including, for example, ongoing conversations between the competent adult and their family and health professionals about goals of future care.” (White et al [5]; page 975).…”
Section: Introductionmentioning
confidence: 98%
“…The first national study of community prevalence found that 14% of Australians had an instructional ACD . A South Australian study found a community prevalence of 12% for instructional ACD in that State and 13 and 11% respectively for two types of appointing ACD (enduring powers of guardianship and medical powers of attorney) . Other research has focused on ACD completion in particular settings, such as residential aged care and hospital .…”
Section: Introductionmentioning
confidence: 99%
“…8 A South Australian study found a community prevalence of 12% for instructional ACD in that State and 13 and 11% respectively for two types of appointing ACD (enduring powers of guardianship and medical powers of attorney). 9 Other research has focused on ACD completion in particular settings, such as residential aged care and hospital. [10][11][12][13][14] There is also limited and inconclusive research on who completes ACD.…”
Section: Introductionmentioning
confidence: 99%